Motivation and Learning Achievement as Determinants of Interest in Continuing Higher Education among Senior High School Students - Dela Getia Latikal; Sudarman; Sutrisno (Journal of Economic Education and Entrepreneurship Studies, 2024)
The purpose of this study was to determine the effect of motivation and learning achievement on the interest of XII grade students of SMA Negeri 3 Samarinda to continue their education to college. The research method used is quantitative. The sample of this study was class XII students of SMA Negeri 3 Samarinda, totaling 142 students. The data used are primary data with data collection techniques using questionnaires and secondary data with data collection techniques using documentation. The analysis method used in this research is multiple linear regression analysis. The results of the simultaneous test (F) obtained a value of 25.018> from 3.06 and has a significant value smaller than 0.05 indicates that the variables of motivation and learning achievement simultaneously affect the interest in continuing studies to college. Thus, this study shows that motivation has a significant effect on the interest of students in class XII of SMA Negeri 3 Samarinda to continue to college, although the effect of the president of learning is partially insignificant.